Scan Mirror Assembly for the Multispectral Scanning Polarimeter of Aerosol-UA Space Mission - Ivan Syniavskyi; Yevgen Oberemok; Yuriy Ivanov; Mikhail Sosonkin; Vladimir Kireyev; Konstantin Akinin (International Journal of Optics)
In this paper, the scan mirror assembly for the space experiment Aerosol-UA scanning polarimeter (ScanPol) is described. The aim of the Ukrainian space mission Aerosol-UA is to create a database of the optical characteristics of aerosol and cloud particles in the Earth’s atmosphere over a long period of time. The optical characteristics of aerosol and cloud particles are derived from multiangular measurements. Multiangular scanning in ScanPol is provided by scan mirror assembly, which contains a reactive torque compensator electric motor and two scan mirrors, mounted on the shaft of the motor. The control system of the scan mirror assembly enables continuous scanning with a constant speed of the space under investigation. This control system tolerates movements of the orbiting satellite and preserves invariability of its spatial position. The polarimeter ScanPol is designed to acquire spatial, temporal, and spectral-polarimetric measurements simultaneously to minimize instrumental effects and “false” polarizations due to scene movement. Instrumental polarization, introduced by the mirrors of scan assembly, is minimized through the polarization compensated two-mirror scheme which contains two mirrors with orthogonal planes of incidence. In this paper, the polarimetric model of the polarization compensated two scan mirrors is considered. Theoretical calculations are given that substantiate the maximum allowable error of the relative angular position of the mirrors is 15 arcmin (0.25°), and the method of adjustment and control of the angular position of the mirrors is proposed. The polarization properties of mirrors are modelled in the spectral range of 370–1680 nm for bulk oxide-free aluminum. It is obtained that the maximum instrumental polarization of the unadjusted mirror system should be observed at 865 nm, and thus, the polarization characteristics of the scanning system at a given wavelength could be considered as representative for ScanPol in general. The key steps for assembling the unit are illustrated.